The role of agricultural cooperatives in sustaining the wheat diversity and productivity: The case of southern Italy - di Falco, Salvatore; Smale, Melinda; Perrings, Charles (Springer, 2008)
We hypothesize that institutions such as agricultural cooperatives influence regional levels of variety diversity through input supply, processing or marketing functions. This diversity can also affect yield, a partial measure of crop productivity. We test these hypotheses with data from southern Italy, a mega-diversity spot and centre of diversity for durum wheat. Cooperatives in the southern regions of Italy process farmers’ harvests of durum wheat into bread, label it, and sell it locally. In this relatively marginalized region of the country, cooperatives enable farmers to capture more of the value of the final product and reduce marketing costs. To test the hypothesis, we apply a two-stage estimation approach with a Cobb-Douglas production function and panel data analysis. Findings suggest that the density of cooperatives in a region is associated with greater spatial diversity in wheat varieties grown, and that, over a 14-year period, this diversity positively affected crop yields.